Safety procedure at construction site rumah keluarga blok A32 di Pangkalan TLDM Lumut, Perak Darul Ridzuan / Mohamad Zaidi Zamhuri - Zamhuri, Mohamad Zaidi (2015)
In a nutshell, this practical training report is about the process and method that involved for the construction of the safety procedure at construction site. I have made this practical training report based on my experiences for 4 months on the site. This practical training report have some parts, it is divided with the company background and my case study background. Based on my experience and observation at the site, the safety first should be important for all any workers, machinery, public or building at site. This can make safe and smoothly during work when to identify hazards and control risks that can arise at construction sites. Before start the work at site, preparing for work is best procedure to follow because it can key to achieving safety and health working conditions is to ensure that safety and health issues are planned, organized, controlled, monitored and reviewed. There have many methods that must to be doing and process to construct the personal protective equipment (PPE) to ant workers doing works at construction site. Besides that, a successful corpprate safety programme should include a clear statement of policy by the client or owner, expreely showing management support for meeting safety objective and the involvement of different stakeholders in the management sysytem. If the contractor also cannot follow the standard operating procedure (SOP) at the construction site, it can give danger or injuries for workers, vehicles, machinery and public surrounding if there is not follow the procedure. This practical training report has been including with the comment and recommendation from my opinion that can solve the problem that arise. In conclusion, I has done cam=n explain with detailed to all the reader about the safety procedures at construction sites.